Gerontological design evaluating the built environment and comfortability of the homes for the aged in Davao City and its potential as a retirement community - Regalado, Krista Anjelik J. (2014)
This study aims to create a retirement community that would adopt to a set of design guidelines based on anthropometry of the elderly and their activities of daily living. Also, it aims to change the negative image of the homes for the aged in the Philippines. As the population of the Philippines increases, it is also projected that the aging population would consequently increase. Considering the present generation, people tend to neglect the needs of the elderly mainly homes for the aged. In achieving efficient architectural solutions, the existing portfolios of homes for the aged were assessed. Mapping and measuring of anthropometric measurements, surveys and interview were conducted to gather the data relevant to the study. It was discovered that there were numerous problems in the physical setting of the facilities. The finishes and configuration of spaces do not conform to the needs and preference of its users. Most of the furniture do not also fit the anthropometry of the elderly. Results of surveys and interviews also pointed out the paradigm of the retirement age bracket on present conditions of the homes for the aged in the country. Majority of them do not wish to stay in Homes for the aged given the existing portfolio of the facility. However, if it would be redesigned into a retirement community that would attend to their needs providing an array of services, the respondents would consider living in this community. With these issues, proper design solutions were proposed and a design guideline was developed for the retirement community. These can then be used for the future planning and design of a retirement community